Grace and agency in Paul and second temple judaism: interpreting the transformation of the heart - Wells, Kyle B. (Supplements to Novum Testamentum, 2015)
Following recent intertextual studies, Wells examines how descriptions of 'heart-transformation' in Deut 30, Jer 31-32 and Ezek 36 influenced Paul and his contemporaries'' articulations about grace and agency